2019
DOI: 10.2478/s11686-018-00009-5
|View full text |Cite
|
Sign up to set email alerts
|

Amoebicidal and Amoebistatic Effects of Artemisia argyi Methanolic Extracts on Acanthamoeba castellanii Trophozoites and Cysts

Abstract: Purpose The present study aimed to investigate the amoebicidal and amoebistatic efects of Artemisia argyi leaf methanolic extract by testing the effects on trophozoites and on cysts. We also determined cytotoxic effect, enzymatic and non-enzymatic antioxidant activities, total phenolic, lavonoid and antioxidative contents of A. argyi. Methods A. argyi was harvested from various geographic sites in Ordu province in Turkey. The fresh leaves were subjected to methanolic extraction. In 100 μl culture, different co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Koloren, et al in a study to investigate amoebicidal and amoebistatic effects of Artemisia argyi methanolic extracts on Acanthamoeba castellanii Trophozoites and Cysts, indicated that Artemisia argyi leaf extract has cytotoxic and anti-amoebic activities. In their study, the growth of trophozoites stopped in Artemisia argyi extract with 50% inhibitory concentrations (IC50)/8 h for 37.4 mg/ ml and 74.8 mg/ml extract solution and had stronger amoebicidal activity on the cysts with IC50/72 h. Also, Artemisia showed stronger inhibitory effects on bronchial epithelial cells at the concentrations of 9.4, 18.7, 37.4 and 74.8 mg/ml [26].…”
Section: Discussionmentioning
confidence: 98%
“…Koloren, et al in a study to investigate amoebicidal and amoebistatic effects of Artemisia argyi methanolic extracts on Acanthamoeba castellanii Trophozoites and Cysts, indicated that Artemisia argyi leaf extract has cytotoxic and anti-amoebic activities. In their study, the growth of trophozoites stopped in Artemisia argyi extract with 50% inhibitory concentrations (IC50)/8 h for 37.4 mg/ ml and 74.8 mg/ml extract solution and had stronger amoebicidal activity on the cysts with IC50/72 h. Also, Artemisia showed stronger inhibitory effects on bronchial epithelial cells at the concentrations of 9.4, 18.7, 37.4 and 74.8 mg/ml [26].…”
Section: Discussionmentioning
confidence: 98%
“…The incidence of Acanthamoeba infection has increased annually, especially in contact lens wearers (Khan, 2006;Ibrahim et al, 2009;Nielsen et al, 2020;de Lacerda and Lira, 2021). Along with the reports on drug resistance (Iovieno et al, 2010;Huang et al, 2017) and the limited anti-Acanthamoeba drugs available (Lorenzo-Morales et al, 2015;Szentmáry et al, 2019), these attract the researcher's attention to focus on the identification of new medicinal plants for therapeutic purposes of Acanthamoeba infection and a compound with greater inhibitory activity and less toxicity is urgently needed (Niyyati et al, 2016;Mahboob et al, 2018;Sanguan et al, 2018;Kolören et al, 2019;Elsheikha et al, 2020). Besides, a treatment strategy of multidrug combination therapy may be needed for drug resistance cases (Tyers and Wright, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Several phytochemicals extracted from many plants have been evaluated as a source of amoebicidal agent, for example Allium sativum, Origanum spp., Arachis hypogaea, Curcuma longa L., Pancratium maritimum L., Pterocaulon polystachyum, Croton isabelli, Artemisia argyi, Piper spp., Citrus spp., Murraya paniculata, Amomum uliginosum, Kaempferia pandurata, etc. (Sanguan et al, 2018;Kolören et al, 2019;Anwar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Plants in the Artemisia genus are recognized for their medicinal value as being anti-protozoal. For example, A. argyi has been used as an anti-amoebic with amoebicidal and amoebistatic effects [49]. Other protozoans have also been treated with Artemisia , and its derivatives were isolated from A. annua with effective results against Plasmodium , Toxoplasma , Cryptosporidium , Giardia and Trypanosoma [50].…”
Section: Discussionmentioning
confidence: 99%